The Concept of Good Faith In Complete Systemic Land Registration In Realizing Legal Guarantee - Arif Firmansyah; Lina Jamilah (Administrative and Environmental Law Review, 2022)
Complete systematic land registration is regulated in Ministerial Regulation Number 6 of 2018 concerning Complete systematic land registration.Ministerial Regulation Number 6 of 2018 concerning Complete systematic land registration. Land registration is a form of implementation of government obligations to ensure certainty and protection of land ownership. The Government has guaranteed the legal certainty by Article 19 of Law Number 5 of 1960 concerning Agrarian Principles. Implementing the Basic Agrarian Law related to complete systematic land registration, in the Minister of Agrarian Regulation No. 6 of 2018 concerning Complete Systematic Land Registration, Article 22 states that if you do not have evidence, then in good faith, make a statement. This study will discuss the excellent faith theory of complete systematic registration in realizing legal certainty.    As a guarantor in complete systematic land registration, the state guarantees the truth of the land registered in good faith.